EFFECT OF SALINITY CONCENTRATION AND WATER TEMPERATURE ON THE RAYLEIGH WING ACCORDING TO FOUR-PHOTON POLARIZED SPECTROSCOPY DATA - Jumanov Khakberdi; Khadjaev Mukhammadzoir; Ergashev Abdulla (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: The purpose of this study is to examine how the temperature of the water and the concentration of NaCl affect the Rayleigh wing line, with an emphasis on how supersonic lattice modulation contributes to the narrowing of the Rayleigh wing and the creation of maxima. Method: To examine the nonlinear optical characteristics of water and aqueous solutions, the study uses four-photon polarization spectroscopy under pre-threshold Brillouin scattering circumstances. The modification of nonlinear cubic susceptibility and its effect on anisotropic scattering were investigated under controlled experimental settings, such as varied salt concentrations and laser beam intensities. Result: The results show that higher water temperatures and NaCl concentrations improve adiabatic compressibility, which in turn raises the Brillouin scattering threshold and decreases the degree of nonlinear cubic susceptibility modulation. Novelty: This study provides new insights into the interplay between the anisotropy of Brillouin scattering, hypersound lattice modulation, and the structural changes in water induced by NaCl concentration and temperature variations, offering a deeper understanding of the microscopic mechanisms influencing water's scattering properties.